Fish assemblage structure in relation to seasonal environmental variation in sub‐lakes of the Poyang Lake floodplain, China. (8th January 2019) - Jin, Bin‐Song; Winemiller, Kirk O.; Shao, Bo; Si, Ji‐Ke; Jin, Jie‐Feng; Ge, Gang
Abstract: The Yangtze River and its watershed have undergone vast changes resulting from centuries of human impacts, yet ecological knowledge of the system is limited. The seasonal variation and spatial variation of three sub‐lakes of Poyang Lake, a huge wetland in the middle Yangtze Basin, were investigated to examine how fish assemblages respond to seasonal hydrology and associated environmental conditions. In all three sub‐lakes, fish assemblage structure revealed strong variations associated with seasonal water level fluctuation. Fish species richness in all sub‐lakes was highest during the middle of the monsoon season and lowest during the dry season. Fish numerical abundance and biomass varied significantly, with several of the most common species having inconsistent patterns of seasonal variation among sub‐lakes. Fish assemblage structure was significantly associated with environmental gradients defined by water level, aquatic macrophyte coverage, conductivity and dissolved oxygen concentration. Assemblage composition in all three sub‐lakes underwent strongest shifts between December and April, the period when water levels were lowest and fishing has the greatest impact on fish stocks. Future impacts that change the hydrology of the middle Yangtze would alter the dynamics of habitat connectivity and affect environmental conditions and fish assemblages of the Poyang Lake wetland system.